2012
DOI: 10.1016/j.bbadis.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal acyl-CoA synthetases

Abstract: Peroxisomes carry out many essential lipid metabolic functions. Nearly all of these functions require that an acyl group – either a fatty acid or the acyl side chain of a steroid derivative – be thioesterified to coenzyme A (CoA) for subsequent reactions to proceed. This thioesterification, or “activation”, reaction, catalyzed by enzymes belonging to the acyl-CoA synthetase (ACS) family, is thus central to cellular lipid metabolism. However, despite our rather thorough understanding of peroxisomal metabolic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 116 publications
1
90
0
Order By: Relevance
“…The selectivity of CG6178 for CycLuc2 over D-luciferin could potentially be exploited for the design of new substrateselective luciferases (10), perhaps by combining features of both beetle luciferases and ACSLs. Furthermore, although we did not observe bioluminescence from the mammalian ACSLs in CHO cells, which have lower homology to firefly luciferase, mammalian ACS enzymes are known to adenylate xenobiotics such as ibuprofen (32,33). We therefore expect that probing the intersection between the luminogenic chemistry of small-molecule luciferin analogs (16,(34)(35)(36)(37)(38)(39)(40) and the activation chemistry of existing adenylating enzymes (33) will reveal that latent luciferase activity is more common than previously thought.…”
Section: Discussionmentioning
confidence: 91%
“…The selectivity of CG6178 for CycLuc2 over D-luciferin could potentially be exploited for the design of new substrateselective luciferases (10), perhaps by combining features of both beetle luciferases and ACSLs. Furthermore, although we did not observe bioluminescence from the mammalian ACSLs in CHO cells, which have lower homology to firefly luciferase, mammalian ACS enzymes are known to adenylate xenobiotics such as ibuprofen (32,33). We therefore expect that probing the intersection between the luminogenic chemistry of small-molecule luciferin analogs (16,(34)(35)(36)(37)(38)(39)(40) and the activation chemistry of existing adenylating enzymes (33) will reveal that latent luciferase activity is more common than previously thought.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, ACSs responsible for S1P metabolism should also be localized in the ER for efficient metabolic flow. It has been reported that each ACS isozyme exhibits characteristic intracellular localization, such as in the ER, plasma membrane, mitochondria, and peroxisome [7,13,14]. However, the precise localization of most ACS isozymes remains unclear since inconsistent localization patterns have been reported among researchers using different approaches.…”
Section: H]dhs Labelingmentioning
confidence: 99%
“…ACSL4 belongs to a five-member family of enzymes that esterifies mainly arachidonic acid (AA) into acyl-CoA [2][3][4][5]. Unlike the other ACSL isoforms, ACSL4 is encoded on the X chromosome and its expression is highest in adrenal cortex, ovary and testis [6][7][8][9][10], as well as in mouse and human cerebellum and hippocampus [11]. Studies on the physiological functions of ACSL4 have revealed possible roles in polyunsaturated fatty acid metabolism in brain, in steroidogenesis, in eicosanoid metabolism related to apoptosis and embryogenesis [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the other ACSL isoforms, ACSL4 is encoded on the X chromosome and its expression is highest in adrenal cortex, ovary and testis [6][7][8][9][10], as well as in mouse and human cerebellum and hippocampus [11]. Studies on the physiological functions of ACSL4 have revealed possible roles in polyunsaturated fatty acid metabolism in brain, in steroidogenesis, in eicosanoid metabolism related to apoptosis and embryogenesis [8][9][10][11][12][13][14]. ACSL4 expression has also been associated with non-physiological functions such as mental retardation disorder [15,16] and cancer [2,3,17,18].…”
Section: Introductionmentioning
confidence: 99%